Influence of house characteristics on mosquito distribution and malaria transmission in the city of Yaoundé, Cameroon - Ngadjeu, Carmene S. (Malar J, 2020)
BACKGROUND: Improving house structure is known to limit contact between humans and mosquitoes and reduce malaria transmission risk. In the present study, the influence of house characteristics on mosquito distribution and malaria transmission risk was assessed in the city of Yaoundé. METHODS: The study was conducted from March 2017 to June 2018 in 32 districts of the city of Yaoundé. Mosquito collections were performed indoor in 10 to 15 houses per district using CDC light traps. A total of 467 houses, selected randomly were used. A pretested questionnaire was submitted to participants of the study to collect information on the household: the number of people per house, education level, type of walls, presence of ceilings and eaves, number of windows, usage of long-lasting insecticidal nets (LLINs), number of bedroom and number of window. Mosquitoes collected were identified morphologically. Anophelines were tested by ELISA to detect infection by Plasmodium parasites. General Estimating Equations adjusting for repeated measures in the same house fitting negative binomial analysis were used to assess the influence of house characteristics on mosquito distribution. RESULTS: A total of 168,039 mosquitoes were collected; Culex spp emerged as the predominant species (96.48%), followed by Anopheles gambiae sensu lato (s.l.) (2.49%). Out of the 1033 An. gambiae s.l. identified by PCR, 90.03% were Anopheles coluzzii and the remaining were An. gambiae sensu stricto (s.s.) (9.97%). The high number of people per household, the presence of screens on window and the possession of LLINs were all associated with fewer mosquitoes collected indoors, whilst opened eaves, the high number of windows, the presence of holes in walls and living close to breeding sites were associated with high densities of mosquitoes indoor. Out of 3557 Anophelines tested using ELISA CSP, 80 were found infected by Plasmodium falciparum parasites. The proportion of mosquitoes infected did not vary significantly according to house characteristics. CONCLUSION: The study indicated that several house characteristics such as, the presence of holes on walls, opened eaves, unscreened window and living close to breeding sites, favored mosquito presence in houses. Promoting frequent use of LLINs and house improvement measures, such as the use of screen on windows, closing eaves, cleaning the nearby environment, should be integrated in strategies to improve malaria control in the city of Yaoundé.